Effect of gonadotrophin releasing hormone to augment semen production in Jersey bulls - BHASKARAN, R; DUBEY, B MUNILAL (The Indian Journal of Animal Reproduction, 2023)
The effect of gonadotrophin releasing hormone (GnRH) to augment semen production in six low and very low semenproducing imported Jersey bulls with normal libido were studied during the year 1999. Bulls were injected single dose of 200 mg GnRH(Buserelin Receptal"' Hoechst) intramuscularly three hours ahead of semen collections. GnRH therapy did not show significantbeneficial effect on libido, reaction time and on other semen characteristics like pH, spermatozoa motility, sperm density, totalsperm concentration, spermatozoa viability and total abnormality of spermatozoa. The mean semen volume and spermatozoamotility in stored semen increased significantly (P
Keywords: Gonadotrophin releasing hormone therapy; Jersey bulls; semen; straw production; libido